Functional 3-Arylisoxazoles and 3-Aryl-2-isoxazolines from Reaction of Aryl Nitrile Oxides and Enolates: Synthesis and Reactivity - Vitale, Paola; Scilimati, Antonio (Synthesis, 2013)
Heterocyclic compounds are crucial starting reagents and intermediates, or they are direct precursors of target chemicals and/or bio-pharmacological active compounds. Today, they are used in the total synthesis of natural products, in drugs or herbicides, and agrochemical preparation. Developing synthetic strategies targeting isoxazoles is a recurrent aim in preparative chemistry. In particular, five-membered heterocycles such as isoxazoles and isoxazolines are easily formed in a two steps or by a ‘one-pot’ procedure, by reacting aryl nitrile oxides with a variety of enolates of carbonyl compounds (i.e., aldehydes, ketones, carboxylic acids), followed by aromatization. Such a methodology was found to be selective and versatile allowing the preparation of pharmacologically active isoxazoles in high yields. 1 Introduction2 Preparation, Synthetic Applications, and Reactivity of 3-Aryl-5-hydroxy-2-isoxazolines and 3-Arylisoxazoles3 Synthesis of 5-Alkyl-3-aryl-5-hydroxy-2-isoxazolines and 5-Alkyl-3-arylisoxazoles4 Synthesis and Reactivity of 3,4-Diaryl-5-hydroxy-2-isoxazolines and 3,4-Diarylisoxazoles5 Synthesis and Reactivity of 3-Aryl-5-hydroxy-5-vinyl-2-isoxazolines and 3-Aryl-5-vinylisoxazoles6 Synthesis of 3-Aryl-4-phenylisoxazole-5-carboxylic Acid7 Conclusions8 Experimental Methodologies
Keywords: 1,3-dipolar cycloaddition; lithium enolates; arylisoxazoles; 3-aryl-5-hydroxy-2-isoxazolines; 3,4-diarylisoxazoles